The relationship between C-reactive protein-albumin-lymphocyte index and peripheral artery disease - Zhe Wu; Lifang Fu; Xiaolei Liu; Changle Gong; Qi Wu; Wei Li; Bin Wang (Scientific Reports)
Abstract The C-reactive protein albumin lymphocyte (CALLY) index is a newly proposed indicator of immune, inflammatory, and nutritional status. However, there is no research on the relationship between CALLY index and peripheral artery disease (PAD). We utilized relevant data from NHANES 1999–2004 on lower limb diseases research. PAD was diagnosed as an ankle-brachial index < 0.9. CALLY index was calculated using the formula: albumin (g/L) × lymphocytes (109/L) ÷ [CRP (mg/L) × 10]. Multivariable logistic regression and restricted cubic splines (RCS) were used to explore the relationship between CALLY index and the risk of PAD. Subgroup analysis was performed based on grouping variables. A total of 5283 participants aged 40 and above were included, with 419 PAD patients and 4864 non-PAD patients. Baseline data showed that PAD patients had significantly higher CALLY values. Multivariable logistic regression results indicated a significant negative correlation between CALLY index and the risk of PAD after adjusting for covariates (OR, 0.813, 95%CI, 0.717–0.923). RCS confirmed a significant linear negative correlation between CALLY index and the risk of PAD (P for nonlinearity = 0.989, P for overall = 0.002). Subgroup analysis revealed that the negative correlation between CALLY index and the risk of PAD remained significant in subgroups of male, white, other races, normal weight, former smoking, now drinking, as well as those with hypertension, without CKD, with or without diabetes, and with or without CVD. In other subgroups, there was also a negative correlation trend between ln CALLY and the risk of PAD. CALLY index is significantly negatively correlated with the risk of PAD. Future research should further validate the clinical application value of the CALLY index.